1990
DOI: 10.1007/bf00146553
|View full text |Cite
|
Sign up to set email alerts
|

Electrooculographic and electroretinographic study in the chicken after dopamine and haloperidol

Abstract: The implication of dopamine in the modulation of the standing potential of the eye was tested in the chicken through an indirect electrooculographic method and direct current electroretinogram (ERG) recording after haloperidol, a mixed D1-D2 antagonist. The standing potential of the eye was reduced within 15 min after intravitreal injection of the antagonist (150 micrograms). This effect is rapidly reversed by an application of dopamine. The fast oscillation was preserved but the light peak was either strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Preliminary data obtained with alpha methyl-para tyrosine (a tyrosine hydroxylase inhibitor) that only blocks DA synthesis are similar to those obtained with blockade of dopaminergic receptors through haloperidoh the SP is reduced and the light peak is depressed. [16] The comparison of the data obtained with these two biosynthesis inhibitors suggests that more than one neurotransmission system is involved in the modulation of the SP and the generation of the light peak.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary data obtained with alpha methyl-para tyrosine (a tyrosine hydroxylase inhibitor) that only blocks DA synthesis are similar to those obtained with blockade of dopaminergic receptors through haloperidoh the SP is reduced and the light peak is depressed. [16] The comparison of the data obtained with these two biosynthesis inhibitors suggests that more than one neurotransmission system is involved in the modulation of the SP and the generation of the light peak.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear how DA affects ocular growth. The mechanism of DA inhibition could lie in the DA modulation of RPE cells as was shown by the effects on RPErelated electrical signals [35,37] or molecular signals [34,35]. Wallman proposed a hypothesis that two signals may be involved in the local connection between the retina and sclera [34].…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in the b-wave was reported by Kupenova and Belcheva [3] in isolated frog eyecups and by Wioland and coworkers [11] in chicks with intravitreal injection, while an increase in the amplitude was described by Schneider and Zrenner [12] in isolated cat eyes and by Starr [2] in isolated rabbit eyes.…”
Section: Discussionmentioning
confidence: 73%
“…Actually, there are marked differences among different species in the distribution of dopaminergic neurons in the retina [16]. Wioland and associates [11] found that intraocular injection of haloperidol in chickens diminished the b-wave. Naarendorp and Sieving [10], however, reported that intravitreal injection of haloperidol increased PII in cats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation